A process to foster pathology-related effects of design primes – how orthopedic patients might benefit from design features that influence health behaviour intention - Rehn-Groenendijk, Jonas; Schuster, Kai; Müller, Helena; Chrysikou, Evangelia (Frontiers in Psychology, 2023)
A growing body of literature mainly in the context of consumer research indicates that the formal-aesthetic and conceptual design of objects can influence users’ thoughts, emotions and even behavioural patterns. While there is strong evidence regarding these effects on actual purchasing decisions, evidence on the effect of aesthetic design features (e.g., haptics, colour) on health-related mental concepts and intentions for health behaviour change is scarce. Based on insights from material and conceptual priming, this article illustrates the research-driven and evidence-based design process of two design primes and comprises pre-tests and an experiment in two settings on the effect of design on health behaviour focusing i.a. on intention for health behaviour change. In an evidence-based and research-driven process, two lecterns were designed to work as primes, i.e., to have a positive vs. negative influence on several mental constructs (sense of control, sense of coherence, resiliency, self-efficacy) and health-related intention. The lecterns differed mainly in terms of aesthetic appearance (e.g., material, colour, proportion, steadiness). They were tested in (a.) a university setting with students (n = 83) and (b.) a clinical setting with orthopaedic rehabilitation patients (n = 38). Participants were asked to perform an unrelated task (evaluation of an unrelated product) while standing at and using the lecterns. Overall, t-tests and Mann–Whitney-U tests show no significant differences but differing tendencies in a mentioning task. When asked to name health-promoting activities, in the clinical setting, participants using the “positive” prime (i.e., the steady lectern, n = 13) mentioned more sport-related aspects on average and a higher portion of sport-related aspects of their answers than participants using the “negative” prime (n = 11). In the university setting (positive: n = 36; negative n = 38), no such differences emerged. This finding gives reason to believe that the prime might be specifically effective in the clinical setting as it relates to physical activity being the most relevant topic of the patients’ pathology.